A Novel Avian Paramyxovirus (Putative Serotype 15) Isolated from Wild Birds - Lee, Hyun-Jeong; Kim, Ji-Ye; Lee, Youn-Jeong; Lee, Eun-Kyung; Song, Byoung-Min; Lee, Hee-Soo; Choi, Kang-Seuk (Frontiers in Microbiology, 2017)
In January 2014, a viral hemagglutinating agent named UPO216 was isolated from fecal droppings of wild birds at the UPO wetland in South Korea during an avian influenza surveillance program. Electron microscopy identified the UPO216 virus as an avian paramyxovirus (APMV). Pathogenicity tests and molecular pathotyping revealed that the virus was avirulent in chickens. A hemagglutination inhibition test assigned the UPO216 virus to a serological group antigenically distinct from known serotypes of APMV (-1, -2, -3, -4, -6, -7, -8, and -9), despite its weak cross-reactivity with APMV-1 and APMV-9. The UPO216 virus RNA genome is 15,180 nucleotides (nts) in length, encodes 3′-N-P(V/W)-M-F-HN-L-5′ in that order, and shows unique genetic characteristics in terms of genomic composition and evolutionary divergence (0.43 or greater from known serotypes of APMV). Phylogenetic analysis revealed that the UPO216 occupies a branch separate from APMV-1, -9, -12, and -13. Serologic surveillance of wild birds (n=880; 15 species, five Orders) detected UPO216-reactive antibodies in 4% (20/494) of serum samples taken from five species of wild duck belonging to the Order Anseriformes. In particular, UPO216-specific antibodies showing no cross-reaction with other serotypes of APMV were detected in four species: Eurasian teal (1/36), European wigeon (1/73), mallard (4/139), and Spot-Billed duck (1/137). These results indicate that the UPO216 virus has antigenically and genetically unique characteristics that are distinct from known serotypes of APMV and is likely circulating widely in wild duck species of the Order Anseriformes. Thus, we propose the UPO216 isolate as a prototype strain of a novel APMV serotype (putative APMV-15).